Pengaruh Pengaruh Pemberian Pakan Komersial Dosis Berbeda Terhadap Pertumbuhan Panjang Mutlak Ikan Rasbora Galaxy (Danio Margaritatus) - inayati, ervin; Muhajir; Hayati, Nurul (Fakultas Perikanan Universitas Pekalongan, 2025)
Rasbora galaxy (Danio margaritatus) is a type of freshwater ornamental fish that has a high economic value and is in great demand in the international market. This fish is included in the omnivorous animal group and can consume natural feed and commercial feed. Commercial feed has the advantage of being able to be designed with a nutritional formulation according to the needs of the type and age of the fish. Among the important factors in feeding management is the dose of feed. Feeding with low or high doses both have a negative effect on the absolute length growth of rasbora galaxy fish. The purpose of this study was to determine the effect of providing commercial feed with different doses on the absolute length growth of rasbora galaxy fish (Danio margaritatus) measuring 1.5-2 cm in experimental tanks. This study used an experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. The treatment in this study was the provision of commercial feed with different doses. Treatment A; 2% of the weight of the test animal biomass, treatment B; 3% of the weight of the test animal biomass, treatment C; 4% of the weight of the biomass of the test animals, treatment D; 5% of the weight of the biomass of the test animals and treatment E; 6% of the weight of the biomass of the test animals. The test animals used 1.5-2 cm galaxy rasbora fish with an average weight of 0.5 g/tail. The stocking density was 2 fish/liter, the experimental media used fresh water with a volume of 3 liters/tub. The results showed that treatment C gave the best results for the absolute length growth galaxy rasbora fish of 0.74 cm/tail. Water quality data obtained water temperature ranged from 26.8 - 27.8 0C, acidity levels ranged from 6.9 - 7.1 and dissolved oxygen ranged from 5.29-5.69 ppm.